(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article is about to show the role of politeness in the sphere of interpersonal communication. Politeness is studied as a strategy or a set of strategies that is orientated towards achieving positive results in communication. The choice of one or another strategy by communicators depends on both outside and inside factors such as parameters of the situation, moral and cultural values. The given research extends and systematizes knowledge about the category of politeness as the most significant element of human relations. The theory of politeness of Brown and Levinson has remained the most seminal and influential starting point for cross-cultural and cross-linguistic contrastive pragmatics. Politeness touches on the issues that are crucial not only for the sociolinguist and social anthropologist but also in the life of human beings communications. In the present study linguistic politeness is crucially conceptualized as a social phenomenon. Theoretical account of politeness provides an obvious picture of linguistic politeness in the communication strategies and distinguishes cases where politeness is communicated from those where it is not. It explains the aspects of politeness phenomenon. It presents an account of politeness phenomena.